2011
DOI: 10.1073/pnas.1019754108
|View full text |Cite
|
Sign up to set email alerts
|

A mathematical model for adaptive prediction of environmental changes by microorganisms

Abstract: Survival in natural habitats selects for microorganisms that are well-adapted to a wide range of conditions. Recent studies revealed that cells evolved innovative response strategies that extend beyond merely sensing a given stimulus and responding to it on encounter. A diversity of microorganisms, including Escherichia coli, Vibrio cholerae, and several yeast species, were shown to use a predictive regulation strategy that uses the appearance of one stimulus as a cue for the likely arrival of a subsequent one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
67
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(73 citation statements)
references
References 32 publications
6
67
0
Order By: Relevance
“…Experimental evolution over multiple generations has been carried out with Drosophila [85], Caenorhabditis [93], mice [66] and plants [59], for instance, suggesting that insightful ER experiments could also be performed with multicellular organisms, despite their relatively longer generation time, provided that the evolutionary dynamics per generation are relatively rapid. Potential lags between an environmental cue and selection on the expressed plastic trait also may be easier to measure or manipulate in multicellular organisms than in microbes (even though such lags have already been measured precisely with the latter [72]). A caveat is that the larger body size of multicellular eucaryotes implies that fewer individuals can be reared per space unit.…”
Section: Choosing the Right Model Organismmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental evolution over multiple generations has been carried out with Drosophila [85], Caenorhabditis [93], mice [66] and plants [59], for instance, suggesting that insightful ER experiments could also be performed with multicellular organisms, despite their relatively longer generation time, provided that the evolutionary dynamics per generation are relatively rapid. Potential lags between an environmental cue and selection on the expressed plastic trait also may be easier to measure or manipulate in multicellular organisms than in microbes (even though such lags have already been measured precisely with the latter [72]). A caveat is that the larger body size of multicellular eucaryotes implies that fewer individuals can be reared per space unit.…”
Section: Choosing the Right Model Organismmentioning
confidence: 99%
“…We are not aware of any quantitative predictions for this evolutionary demographic effect. Evolutionary theory has investigated the role of environmental predictability for the evolution of plasticity, but without demography [11,30,31,72]; Reed et al [15] performed simulations on the interaction of plasticity and population growth in a fluctuating environment, but without evolution, and without changes in patterns of environmental variation. Despite the lack of quantitative predictions, basic qualitative predictions could be tested experimentally.…”
Section: Some Outstanding Questions In Need Of Testingmentioning
confidence: 99%
“…It has been demonstrated that bacterial populations respond faster to a change of nutrient source when the forthcoming nutrient source has been presented in the recent past (2,3). Similarly, bacterial populations that were exposed to sublethal stress levels showed increased survival of a higher stress level of the same type (4)(5)(6). Theoretical and experimental studies indicate that basing cellular decisions on environmental cues perceived in the past can be advantageous in dynamic environments (3,7,8), suggesting that such history-dependent behavior can be the result of adaptive evolution in dynamic environments.…”
mentioning
confidence: 99%
“…Some microbes occupy reasonably predictable niches in which one environmental input is generally followed by a second input. In such cases, fungi that have evolved to anticipate the second input following exposure to the first would have a fitness advantage (206) Domesticated brewing yeasts provide an excellent example of this “adaptive prediction” because, as they ferment sugars, they become exposed to increasing ethanol concentrations (input 1) and then, when the sugars are exhausted, they switch to respiratory metabolism and become exposed to oxidative stress (input 2). Presumably as a consequence of this environmental predictability, S. cerevisiae has evolved to activate oxidative stress genes following exposure to ethanol (207).…”
Section: Adapting To Individual Stressesmentioning
confidence: 99%